AWARENESS OF INDOOR AIR POLLUTION AND FACTORS ASSOCIATED WITH THE USE OF UNCLEAN COOKING FUELS AMONG RESIDENTS OF MBALALA TOWN, MUKONO DISTRICT, UGANDA: A CROSS-SECTIONAL STUDY. - Namazzi, Gloria; Musoke, David; Matovu, Joseph K.B (Student’s Journal of Health Research Africa, 2024)
Background In most low- and middle-income countries, many households still rely on unclean cooking fuels (such as firewood and charcoal) despite the associated indoor air pollution exposure. We assessed people’s awareness of indoor air pollution and factors related to the use of unclean cooking fuels among residents of Mbalala town, Mukono district. Methods This was a descriptive cross-sectional study in which we collected both quantitative and qualitative data. Quantitative data were collected on socio-demographic characteristics, awareness of indoor air pollution (effects, causes, risks, control measures), and cooking practices (including the use of clean/unclean cooking fuels) from 385 respondents. We computed the proportions of respondents who were aware of indoor air pollution, and who used unclean fuels, and determined the factors associated with using a modified Poisson regression model. Qualitative data were collected from 10 key informants (community leaders and village health teams) and analyzed manually following a thematic framework approach. Results The mean age was 32.5 years (SD: ±11.5). Three-quarters of the respondents (75.3%, n=290) were aware of indoor air pollution. Awareness of indoor air pollution was associated with being 46 years or older, being male, having a tertiary/University education, and earning between US104 and US209 monthly. Ninety-four percent (n=350) used unclean cooking fuels. Use of unclean cooking fuels was significantly lower among men than women, and among respondents with primary/secondary education than those without education. Qualitative findings showed that participants used unclean cooking fuels because they were cheaper and accessible. Restrictions on the use of electric appliances by landlords and lack of electricity limited the use of gas cookers or other electric appliances. Conclusion Despite the high awareness of indoor air pollution, nearly all respondents reported using unclean cooking fuels. Recommendation Community sensitization on the health risks associated with the continued use of unclean cooking fuels is urgently needed.